THE VOICE OF ELT STUDENTS AT ISLAMIC COLLEGE ON ACADEMIC LIFE - IRWANSYAH, DEDI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Research shows that student voice might be an influencing factor in the future transformation and innovation of English language teaching (ELT). The voice has long been believed to be an instrument that could provide ELT practitioners and policymakers with meaningful feedback for the betterment of curricula, materials, and classroom practices. However, there are limited discussions exploring ELT student voice in such particular educational contexts as Islamic colleges. This article aims to contribute to our understanding of that rarely discussed voice with a particular focus on: (a) the students‟ best experience as English education students at an Islamic college; (b) the students‟ perceptions related to dress code and exams; and (3) the students‟ self- assessment of English language skills. This study presents a survey study on 278 students in the English language education department at an Islamic college in Lampung province, Indonesia. The data are drawn from a survey consisting of open-ended questions distributed to the respondents at the end of the semester. Data analysis was conducted qualitatively, ranging from preparing and organizing the data to interpreting the meaning of the data in line with the research questions and theoretical review. The findings reveal that among the students' best experiences were the Islamic atmosphere, affordable tuition fees, religious education, professional lecturers, and scholarship availability. The majority of students agreed with the dress code regulation and had problems with cheating on the final examinations. The findings also show that more than half of the respondents are not sure about their English competency. This study offers important implications for English teacher education in Islamic educational contexts.